Digital archives in the cloud: Collective memory, institutional histories and the politics of information. Issue 10 (24th August 2019) - Peters, Michael A.; Besley, Tina
Abstract: The archive is a cultural institution that creates a framework for the social and collective memory and as such is one of the collection of knowledge institutions that not only preserves and classifies "texts" but uses them to re-create collective memory and sometimes to invent cultural histories. Like all knowledge institutions, the archive is also a construction deeply implicated in knowledge politics or what Foucault calls power/knowledge. In the past the archive has functioned as a central metaphor for the construction of human knowledge in all it is different institutional forms and like the encyclopedia and the camera, the archive produces highly coded representations that make implicit validity claims to the truth and justice of the past. Politically speaking, those who control the archive control the past. In the digital world, the archive is used to describe a machine-readable location as a store for "data" and "information." Digital technologies radically alter our existing institutions, making access to their embedded knowledge widely available and enable learning and research anytime, anywhere. Data analytics algorithmically can manipulate electorates and entire democracies in new ways, while destabilising the free press. This article asks what digitizing an archive means for collective memory, for the history of institutions and for politics in the Cloud.